1988
DOI: 10.1111/j.1365-2028.1988.tb00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximum rate of increase in the African Elephant

Abstract: Summary The theoretical maximum rate of increase for the African elephant is calculated at 7%. This figure agrees closely with the rate of increase observed at Addo Elephant Park, the highest rate of increase reported for elephants living under natural conditions. An elephant population increasing at the maximum rate soon reaches a stable age distribution in which 48% of the animals are older than 11 years of age, (the age of first reproduction) and 6.7% are calves (less than one year old). Several papers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 2 publications
3
40
0
Order By: Relevance
“…Generalised linear models with normal error structure were conducted for (a) the total study area survey population estimates and (b) for the management area NG11 survey population estimates, with year of survey fitted as the explanatory variable and significance tested at p \ 0.05. We calculated the maximum growth rate for an elephant population at 7 % by Calef (1988), using a minimum inter-calving period of 3 years (ranges between 3 and 4.7 years) and a mean age of first birth of a calf at 11 years (ranges between 8 and 14 years). We compared the estimated population growth rate to this predicted maximum rate of increase.…”
Section: Population Growthmentioning
confidence: 99%
“…Generalised linear models with normal error structure were conducted for (a) the total study area survey population estimates and (b) for the management area NG11 survey population estimates, with year of survey fitted as the explanatory variable and significance tested at p \ 0.05. We calculated the maximum growth rate for an elephant population at 7 % by Calef (1988), using a minimum inter-calving period of 3 years (ranges between 3 and 4.7 years) and a mean age of first birth of a calf at 11 years (ranges between 8 and 14 years). We compared the estimated population growth rate to this predicted maximum rate of increase.…”
Section: Population Growthmentioning
confidence: 99%
“…Calef (1988) predicted a maximum rate of increase for elephant populations of 7 per cent. Despite the closed nature of the Addo elephant population and the current high density (2.8 elephants per sq km), the observed population growth rate is relatively rapid, indicative of a healthy, growing population.…”
Section: Demographic Analysismentioning
confidence: 99%
“…Previous research done in northern Botswana showed that the resident elephant populations has been increasing (Calef 1988;Melton 1975), and some reports cautioned about excessive woodland utilization by elephants and loss of woodland if elephant numbers were allowed to increase beyond a certain, yet unknown threshold (Child 1968;Moroka 1984;. Recent research (Ben-shahar 1993) has shown that elephants were inclined to utilize particular plant species and the proportion of the plants damaged by elephants depended on the distance of plants from water sources.…”
Section: Introductionmentioning
confidence: 99%